Effect of Commonly used Pesticides on the Biochemical Profile of a Few Vegetables Grown in Kanniyakumari District of Tamil Nadu (Indo-American Journal of Life Sciences and Biotechnology, 2024)
The present investigation was carried out to find out the effect of commonly used pesticides on the morphological, biochemical and phytochemical parameters of vegetable crops like Amaranthus gangeticus L. Solanum melongena L. and Lycopersicon esculentum Mill. which are commonly grown in Kanyakumari District of Tamil Nadu. The experiments were conducted using control group of the above said vegetables exposed to biopesticide flower extract of Tagetes minuta, and an experimental group in which the above said vegetables plants were exposed to three commonly used pesticides – Monocrotrophos, Cypermethrin and DDT at varying concentrations during pest infestations. The harvested useful parts from experimental and control vegetable crops were evaluated biochemically and phytochemically. The above said vegetables procured from local market was also screened. Results from this evaluation indicated that crop exposed to chemical pesticides exhibited a variation in the biomolecules and phytochemicals evaluated. Protein, Total Chlorophyll, carbohydrate, Proline, Total Phenolic content and Total Flavanoid content of control plants treated with Tagetes minuta flower extract were normal values. While the experimental plants exposed to pesticides showed a decrease in the level of chlorophyll and carbohydrate content, while there was an increase in stress amino acid (Proline) and the Total protein content. However, the Total Phenol content and Total Flavonoid content increased with increasing concentration of pesticides, but at still higher levels of pesticides there was a decrease in these biomolecules. Phytochemically, secondary metabolites like terpenoids, alkaloids, phenolic compounds, steroids, flavonoids, saponins, catechins showed increased accumulation in the experimental plants exposed to pesticides at lower levels of pesticides. The various biological parameters evaluated characters showed variation in the control and experimental plants, which is probably because of the ill effects of pesticides in the experimental group of vegetables and the good effects of biopesticide used in the control group vegetables. This work is only basic study which needs further sustainable study into the topic to bring out the impact of chemical pesticides by assessing their residue level in the experimental plants.